Investigation of antioxidant capacity of brown capped button mushroom candidate varieties - Mikola Erika; Geösel András; Fodor Marietta; Stefanovits-Bányai Éva; International Symposium on Analytical and Environmental Problems (25.) (2019) (Szeged) (2019)
The button mushroom (Agaricus bisporus) is one of the most widely cultivated mushrooms in the world thanks to its high endogen components. Ingredients of the mushroom with ferric reducing capacity in brown button mushroom can stop or delay the effects of oxidative damage, therefore they play an important role in maintaining health care. During the research process, was used the activity of enzymes participating in antioxidant defense (peroxidase, polyphenol oxidase) and polyphenol content known from non-enzyme defense to describe the reducing properties of brown capped button mushroom candidate varieties, along with the FRAP method based on ferric reducing capacity. Our goal is to compare the number of bioactive substances and substances with significant reducing capacity based on the examined parameters of the button mushroom candidate varieties and, based on the compounds with significant reducing properties to identify the best candidate varieties. According to our results it can be concluded, that there is a strong connection between the measured parameters and the individual candidate varieties, based on which we can choose the candidate variety deemed best.